The use of durable barrier cream in preventing pressure ulcer - Mazlinda Musa; Ayu Sulaini J; Suriawati G; Mardiana M; Zahri MK (2018)
A pressure ulcer is a common health problem, particularly among the physically limited or bedridden individuals. The most vulnerable group to suffer this condition is the elderly. The prevalence of Geriatric inpatient with pressure ulcer stage I, II, III or even IV for a month was 35.5% of the total admission. The understanding of recovery process, prevention remains the best management strategy as it improves their quality of life. This study aims to compare PU development outcomes in geriatric patients nursed on either using the Durable barrier cream (Cavillon cream) or non-pharmacological intervention alone. Using the Quasi experimental study-design, the selected participants were subjected to Cavaillon cream as well as the intervention. The assessment used were the outcome of the pressure ulcer was assessed using the measured size of the redness area. There was the statistically significant reduction in pressure ulcer size on day three compared to the size on day one among the intervention group, z value was -5.028, p<0.005.A systematic assessment and intervention were found to be effective in improving the healing process of the pressure ulcers, while providing high satisfaction in the practiced setting.